MicroRNA-26 Family Is Required for Human Adipogenesis and Drives Characteristics of Brown Adipocytes. (23rd May 2014) - Karbiener, Michael; Pisani, Didier F.; Frontini, Andrea; Oberreiter, Lisa M.; Lang, Eleonore; Vegiopoulos, Alexandros; Mössenböck, Karin; Bernhardt, Gerwin A.; Mayr, Torsten; Hildner, Florian; Grillari, Johannes; Ailhaud, Gérard; et al.
Abstract: Adipose tissue contains thermogenic adipocytes (i.e., brown and brite/beige) that oxidize nutrients at exceptionally high rates via nonshivering thermogenesis. Its recent discovery in adult humans has opened up new avenues to fight obesity and related disorders such as diabetes. Here, we identified miR-26a and -26b as key regulators of human white and brite adipocyte differentiation. Both microRNAs are upregulated in early adipogenesis, and their inhibition prevented lipid accumulation while their overexpression accelerated it. Intriguingly, miR-26a significantly induced pathways related to energy dissipation, shifted mitochondrial morphology toward that seen in brown adipocytes, and promoted uncoupled respiration by markedly increasing the hallmark protein of brown fat, uncoupling protein 1. By combining in silico target prediction, transcriptomics, and an RNA interference screen, we identified the sheddase ADAM metallopeptidase domain 17 (ADAM17) as a direct target of miR-26 that mediated the observed effects on white and brite adipogenesis. These results point to a novel, critical role for the miR-26 family and its downstream effector ADAM17 in human adipocyte differentiation by promoting characteristics of energy-dissipating thermogenic adipocytes. Stem Cells   2014;32:1578–1590